Economic cooperation of the Republic of Serbia and the People’s Republic of China - Mali, Siniša (Napredak, 2024)
In the past decade, the cooperation between Serbia and China has become a key factor in the economic development of our country. Serbia is the first country in Central and Eastern Europe to establish a strategic partnership with China in 2009. A special momentum has been recorded since 2013, while in 2016 this was raised to the level of comprehensive strategic partnership, which represents the backbone of our extremely successful cooperation. The rise of bilateral relations, as China is currently one of the most important economic partners of Serbia, measured both by the volume of commodity exchange and the value of Serbian exports, as well as by the value of investments and joint projects, has been significantly contributed to by the steel friendship of the two countries and strong political support at the highest level by the President of the Republic of Serbia Aleksandar Vučić and the President of the People’s Republic of China Xi Jinping.